Meet the expert Liz Fong-Jones on cultivating production excellence - Fong-Jones, Liz (O'Reilly Media, 2020)
"Taming the complex distributed systems you're responsible for requires changing not just the tools and technical approaches we use but also who's involved in production, how they collaborate, and how we measure success. Expert Liz Fong-Jones explores several practices core to production excellence: giving everyone a stake in production, collaborating to ensure observability, measuring with service-level objectives, and prioritizing improvements using risk analysis"--Resource description page